2022
DOI: 10.3390/jcm11030760
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Magnetic Resonance Imaging in Juvenile Idiopathic Arthritis Versus Non-Juvenile Idiopathic Arthritis Patients with Arthralgia

Abstract: This retrospective case–control study aimed to evaluate whether Magnetic Resonance Imaging (MRI) enables differentiation of ankle arthritis in Juvenile Idiopathic Afrthritis JIA from ankle arthralgia of unknown aetiology in patients clinically suspected of JIA. Forty-four children, at ages 5–16, who underwent MRI of the ankle from January 2016 to March 2021 for clinically suspected active ankle arthritis in the course of JIA were included. MRI findings in both groups—patients with the final diagnosis of JIA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In pediatric settings, the spectrum of potential arthritis diagnoses can be relatively broad, primarily including infectious and inflammatory causes and, to a lesser extent, oncological diseases [34][35][36][37]. With respect to inflammatory causes, distinguishing between JIA and other types of arthritis can prove to be a challenge, mainly because of the lack of specific antibodies in several JIA subtypes [35,38]. Over time, research has focused on investigating potential markers to assist clinicians in discriminating arthritis patients more accurately [13,39].…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric settings, the spectrum of potential arthritis diagnoses can be relatively broad, primarily including infectious and inflammatory causes and, to a lesser extent, oncological diseases [34][35][36][37]. With respect to inflammatory causes, distinguishing between JIA and other types of arthritis can prove to be a challenge, mainly because of the lack of specific antibodies in several JIA subtypes [35,38]. Over time, research has focused on investigating potential markers to assist clinicians in discriminating arthritis patients more accurately [13,39].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to create a similar MRI summarized score for the ankle that enables discrimination between ankle arthritis in JIA from non-JIA patients with clinically suspected arthritis. The findings of Ostrowska et al [ 48 ] confirm that MRI diagnosis of JIA remains a challenge, and with the exception of tendinitis, other MRI features are nonspecific for JIA, and thus the scoring system has proven inadequate.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…38 Ostrowska et al reported that MRI showed tenosynovitis was significantly more present in children diagnosed with JIA (p ¼ 0.031). 44 Tenosynovitis, which usually occurs in at least 50% of the patients, mainly affects the tibialis posterior, peroneus longus, and brevis. 44 Effusion and synovitis can be reliably distinguished on MRI only with gadolinium, but the potential harm caused by deposits in the brain is still unknown.…”
Section: Pediatric Rheumatic and Autoimmune Diseasesmentioning
confidence: 99%
“…44 Tenosynovitis, which usually occurs in at least 50% of the patients, mainly affects the tibialis posterior, peroneus longus, and brevis. 44 Effusion and synovitis can be reliably distinguished on MRI only with gadolinium, but the potential harm caused by deposits in the brain is still unknown. Thus, Panwar et al suggested using the term "effusion/synovial thickening" that does not necessarily require the use of contrast.…”
Section: Pediatric Rheumatic and Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation